Implementing concepts from green logistics in the turkey production supply chain - Wilson, Griffin; Horsey, Bazyl; Stone, Richard (Frontiers in Sustainability, 2024)
The global turkey market represents a sector of increasing growth in the previous decade, and projections for the next decade reflect the probable continuation of this growth. Industry trends also indicate the globalization of turkey meat production, as the loci of production has continually shifted from one dominated by the United States to one with an increasing number of production units globally. In contrast with other popular meat products, comparatively fewer resources have been devoted to academic research concerning the growth, production, distribution, and sale of turkey and turkey products. This lack of research is particularly notable in the area of supply chain management and environmental sustainability. Given the increasing volume of turkey production and lower volume of academic interest, it stands to reason that there remain many opportunities for improvement across the value chain in this industry. In this paper, we take a "green logistics" approach in investigating one such opportunity by using data provided by one of the largest turkey producers in the United States to formulate a mixed-integer program aimed at minimizing the environmental impact of turkey products in a segment of the product supply chain. Implementation of the resulting brooder-finisher farm assignments developed by the model would yield an average 50% decrease (184 metric ton) in greenhouse gas emissions at the operation under investigation while also addressing other areas of significant vulnerability for the industry (production costs, biosecurity risk, and animal wellbeing). As consolidated turkey meat production systems continue to expand globally, we argue that a similar approach could readily be deployed by these growing and emerging production systems.1 See section 2.3 for a detailed description of the turkey production process, including definitions of the terms "brooder" and "finisher."2 Feed efficiency is a measure of how much saleable product is produced per unit of feed consumed.3 See section 2.4 for a more thorough treatment of this topic.